Performance indicators for the men's shot put in the USA development system - Babbitt, D.; Johnson, L. (New Studies in Athletics, 2016)
Unlike most other nations, the USA relies heavily on the sport programmes of its educational institutions for the development of track and field athletes. This is especially true for technical disciplines such as the shot put. The desire of athletes to produce results that justify the university sport scholarships available or attract sponsorship that will enable them to continue their careers after graduation from university is a key element of the system. The authors examine the development of the top 74 male shot putters who came through the system in the period 2012 to 2017, some who have or are likely to go on to international level performances, with the aim of helping American coaches identify talent for their university programmes. Their findings, which suggest that male shot putters between the ages of 19 and 23 years in the American system progress faster than those in other countries, also give coaches insight on expected performance development. However, the study was unable to find a significant correlation between performance with the 5.4kg shot used in high schools and eventual performance with the international implement by the end of the athlete's university career.